Parental instrumentalization, a pattern of interaction within the family - Barzola Matos, José Luis (2017)
This article presents the construct parental instrumentation as a categorization of a problematic inside families. This phenomenon has already been noticed by different psychological perspectives and currents, but a consensus has not been reached. Most of the orists and researchers in the area have described and explained different states of the same from their own theoretical perspectives, but allude to a same phenomenon, which is proposed to denominate parental instrumentation, defining the phenomenon in function of its main characteristic. Finally, it is concluded this construct will allow to cement the necessary theoretical bases to enable applications in the clinical-systemic intervention with families that suffer from it.